Germany's other modernity : Munich and the making of metropolis, 1895-1930 - Jerram, Leif (Manchester University Press, 2018)
This book is about what it meant to build a city in Germany at the turn of the twentieth century. It explores the physical spaces and mental attitudes that conditioned beliefs about the past and expectations for the future in the crucial German generations that shaped the young Reich, fought the Great War, and experienced the Weimar Republic.